Upaya Meningkatkan Motivasi Belajar dan Kemampuan Menulis Permulaan Siswa Melalui Penerapan Media Pembelajaran Kartu Kata Pada Kelas I SDN 170 Bengkulu Utara - Parlena Parlena (Journal of Elementary School (JOES), 2020)
This study aims to prove whether the application of word card learning media in Indonesian language learning can increase students' motivation and pre-writing skills. The research design used was classroom action research with two learning cycles. The research subjects in this study were students of class I SD Negeri 170 Bengkulu Utara which consisted of 20 students. The research was conducted for two months starting from September 2019 to November 2019. The results showed that the word card learning media was proven to be able to increase student learning motivation in Indonesian language learning, where in the initial test the percentage of student learning motivation was 40%, increasing in cycle I by 60% and increased in cycle II by 85%. The learning media for word cards were also proven to be able to improve students' initial writing skills in Indonesian language learning, where in the initial test the classical completeness level was 35%, increased in cycle I to 55% and in cycle II increased to 85%. In conclusion, the learning media for word cards were effective in increasing learning motivation and initial writing skills of SD Negeri 170 Bengkulu Utara Keywords: word cards, writing skills, instructional media, learning motivation.